ANALISIS DISIPLIN KERJA PEGAWAI PADA BKPSDM KARAWANG - Ubadilah, Najwa; Pertiwi, Wike; Augie Putrie, Rena (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the level of employee work discipline at the Human Resources Development and Personnel Agency (BKPSDM) of Karawang, particularly regarding the timeliness of clock-out attendance. Work discipline is an essential aspect that supports the effectiveness of public services; therefore, an evaluation of employee behavior and the attendance system used is necessary. This research employs a descriptive qualitative method with data triangulation through observations, interviews with five informants, and employee attendance records from 2024. The findings indicate that employee discipline is still not optimal, as reflected by the high frequency of late clock-out attendance each month. The dominant contributing factors include employee negligence and the absence of an automatic notification feature in the SIAP attendance application, which often causes employees to forget to clock out. The study concludes that such indiscipline negatively affects work effectiveness and highlights the need for improvements to the attendance system and increased employee awareness of discipline. The contribution of this research includes strategic recommendations such as developing an automatic reminder feature in the SIAP application, strengthening supervisory control by superiors, and providing continuous socialization to enhance discipline, performance, and employee professionalism.